Effects of transition metals on nitric oxide synthase catalysis - Perry, Jason M. (The National Academy of Sciences, 1998)
The biosynthesis of nitric oxide (NO) by the enzyme NO synthase (NOS) proceeds by the hydroxylation of l-arginine to form N(G)-hydroxy-l-arginine followed by the conversion of N(G)-hydroxy-l-arginine to l-citrulline and NO. The previously identified requirements of this relatively complicated reaction include several protein-bound cofactors: cytochrome P450-type heme, flavin mononucleotide (FMN), flavin adenine dinucleotide (FAD), and tetrahydrobiopterin (H(4)B). In addition to l-arginine, NOS also requires the substrates NADPH and molecular oxygen. The role of H(4)B in NOS catalysis has long been a subject of debate and uncertainty fueled, in part, by the failure to detect any dependence of the NOS reaction on nonheme iron, a cofactor integral to catalysis in every other H(4)B-dependent enzyme. Here we report the ability of NOS to bind transition metals stoichiometrically, and demonstrate that the rate of catalysis is enhanced by nonheme iron. We also show that other divalent transition metals, including Cu, Zn, Co, and Ni, inhibit NOS catalysis. Also, the addition of Cu(2+) to NOS inhibits heme reduction, whereas the addition of Fe(2+) does not. Overall, the results appear to connect NOS to the known H(4)B/nonheme iron-dependent hydroxylases, and suggest a similar, if not identical, step in the NOS reaction mechanism.